2021
DOI: 10.1530/ec-20-0569
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome components with circulating levels of cytokine clusters in young women

Abstract: Background: The purpose of this study was to investigate the relationship between circulating zinc α 2-glycoprotein (ZAG), Irisin, betatrophin and adiponectin concentrations and metabolic syndrome (MetS) components and to analyze the effects of blood glucose and insulin on these cytokine concentrations in vivo. Methods: A total of 196 young women, including 78 healthy women and 118 women with MetS components, were recruited for this cross-sectional study. An oral glucose tolerance test and euglycemic-hyperins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Similar findings were shown by previous study 8 . Animal studies have shown that ZAG act as a regulator of lipid metabolism, and our results multiplied these finding and we showed significantly positive correlation between ZAG and triglyceride, and inverse correlation with HDL-cholesterol 18 , 19 . These clinical finding suggest that ZAG may play an important regulatory role in lipid metabolism in humans as well.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings were shown by previous study 8 . Animal studies have shown that ZAG act as a regulator of lipid metabolism, and our results multiplied these finding and we showed significantly positive correlation between ZAG and triglyceride, and inverse correlation with HDL-cholesterol 18 , 19 . These clinical finding suggest that ZAG may play an important regulatory role in lipid metabolism in humans as well.…”
Section: Discussionsupporting
confidence: 88%
“…This controversy between the findings could be due to differences in the study design, including sample size, age, and more importantly subjects involved in the two studies were from different population. Age effect on ZAG levels was confirmed in a recent study by Tan et al 18 were they reported significantly lower circulating ZAG level in young women with MetS components. Whereas, in agreement with findings of our study, the results of Yeung et al 8 study on Chinese subjects have shown that ZAG levels were significantly elevated in MetS subjects and it was also elevated progressively with an increasing number of components of the MetS.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This controversy between the ndings could be due to differences in the study design, including sample size, age, and more importantly subjects involved in the two studies were from different population. Age effect on ZAG levels was con rmed in a recent study by Tan et al 15 were they reported signi cantly lower circulating ZAG level in young women with MetS components. Whereas, in agreement with ndings of our study, the results of Yeung et al 7 study on Chinese subjects have shown that ZAG levels were signi cantly elevated in MetS subjects and it was also elevated progressively with an increasing number of components of the MetS.…”
Section: Discussionmentioning
confidence: 75%
“…Infusion of proinflammatory cytokines such as IL-6 or TNF-α induced an increase in levels of AT1-AA in animal models, suggesting that some inflammation-related cytokines may be involved in this process (Irani et al, 2010;Lamarca et al, 2011). In MetS patients, an increase in several pro-inflammatory cytokines has been previously observed various studies (Bassols et al, 2010;Saunders et al, 2018;Tan et al, 2021). In the rat MetS model, we observed an increase in levels of serum IL-17, IL-1β, IL-6, TNF-α and LIGHT (TNFSF14), which may be involved in the increase in levels of circulating AT1-AA in these rats.…”
Section: Discussionmentioning
confidence: 88%